2000
DOI: 10.1002/1097-0215(20000915)87:6<869::aid-ijc17>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Call and recall for cervical cancer screening in a developing country: A randomised field trial

Abstract: A randomised field trial was used to assess Mexican women's response to a mailed invitation for a Papanicolaou test. A sample of 4,802 women, 20 to 64 years old, chosen at random from the Mexican Social Security Institute Register were randomly assigned to an intervention and to a control group. A letter of invitation and a reminder were sent to the intervention group. A letter was also sent to the control group at the end of the follow‐up period (8.5 weeks) in order to compare the response among women who rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Three articles were excluded because they evaluated combinations of interventions and did not examine letter reminders separately 7–9 . Three papers were not analyzed because the study population was not restricted to those due for Pap smear screening 10–12 . Inquiries for any unpublished studies on the subject were made of authors whose names were obtained from the literature review.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles were excluded because they evaluated combinations of interventions and did not examine letter reminders separately 7–9 . Three papers were not analyzed because the study population was not restricted to those due for Pap smear screening 10–12 . Inquiries for any unpublished studies on the subject were made of authors whose names were obtained from the literature review.…”
Section: Resultsmentioning
confidence: 99%
“…Two previous studies conducted in Sweden [19] and Mexico [20] have reported the proportion of women attending cervical screening following an invitation and/or reminder to be in the order of 31%. Sample size was calculated using OpenEpi v.2.3.1 [21]; based on a 1 : 1 ratio of case to control participants, the study would need approximately 200 participants (inclusive of an additional 20% to account for non-respondents and design effect of two [22]) in the intervention and comparator arm to have over 80% power at the 95% confidence level (alpha 0.05, two sided) to detect an effect size of 31%.…”
Section: Methodsmentioning
confidence: 99%
“…A rural individual's need to drive may have been an added motivation to use the CPAP machine to maintain their driver's licenses. Previous studies have also suggested that people living in rural areas are more responsive (Torres-Mejia et al, 2000) and compliant (Ramaiah et al, 2000) to treatment than people who live in urban centers. Consequently, the results in this study may have been influenced by the rural location of our study sample and may reflect a novel finding in this regard.…”
Section: Effect Of Rural Locationmentioning
confidence: 99%